Preconception assessment of reproductive genetic risk in primary care - Hussein, Norita (2016)
Optimizing maternal health and improving reproductive outcomes are widely acknowledged as major challenges in the health care system. Care during the antenatal period has been the focus of improving maternal health and reproductive outcomes. Yet, evidences have shown that antenatal care alone is not enough. Initiating care before conception or preconception care could be potentially effective to further improve maternal health and reproductive outcomes.